2013
DOI: 10.1002/ece3.914
|View full text |Cite
|
Sign up to set email alerts
|

Is the hibiscus harlequin bug aposematic? The importance of testing multiple predators

Abstract: Aposematism involves predators learning conspicuous signals of defended prey. However, prey species utilize a wide range of chemical (or physical) defenses, which are not likely to be equally aversive to all predators. Aposematism may therefore only be effective against a physiologically sensitive subset of potential predators, and this can only be identified through behavioral testing. We studied the emerging model organism Tectocoris diophthalmus (Heteroptera: Scutelleridae), an aposematically colored but we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…) and aposematic (Fabricant et al. ), which renders them unpalatable to avian predators (Fabricant & Smith ), which may reduce the potential predation risk associated with guarding. Furthermore, it is unusual to see unguarded egg clutches in the field at any time of year (R. Giffney, pers.…”
Section: Discussionmentioning
confidence: 99%
“…) and aposematic (Fabricant et al. ), which renders them unpalatable to avian predators (Fabricant & Smith ), which may reduce the potential predation risk associated with guarding. Furthermore, it is unusual to see unguarded egg clutches in the field at any time of year (R. Giffney, pers.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, there are also remarkable differences in the responses of some of these predators. For example, jumping spiders have limited ability to retain learned aversions compared with birds [20], and mantids will readily feed on aposematically colored harlequin bugs that are noxious to birds [18]. Collectively, these results highlight the novel and unexpected insights that can be gained from examining diverse predators.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have emphasized the importance of considering a more diverse set of predators in this work [16,17], with a particular emphasis on considering terrestrial invertebrate predators [18][19][20][21][22][23][24], and such studies are revealing surprising insights. In some cases, there are remarkable similarities between arthropod predators and birds; for example, similar (but not identical) patterns of color aversion, learning, and generalization have been shown in jumping spiders [19][20][21]24], mantids [25], and predatory wasps [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Harlequin bugs (Tectocoris diophthalmus) painted bright orange, placed on a leaf, were cryptic to mantids from afar but could induce avoidance learning in birds. In the same system, Fabricant and Smith (2014) found that the same bugs (naturally colourful and iridescent) were conspicuous (hence aposematic) to domestic chicks but not mantids, which emphasizes the importance of testing multiple, ecologically relevant predators.…”
Section: Chapter 1: a Review Of Invertebrate Predation On Aposematic mentioning
confidence: 93%
“…The practice of considering more than one predator type (and its' subsequent behaviour) has been less prevalent in the study of animal coloration and aposematism as literature has continually focused on behaviour and cognition from a single perspective and far fewer studies have investigated other prey taxa. Fabricant and Smith (2014) discovered that aposematic Harlequin bugs were aposematic to domestic chicks but not to praying mantids (they also observed assassin bugs, lynx spiders, and orb-web spiders feeding freely on these bugs). Further, Pearson (1985) offered tiger beetles (Cicindela spp.)…”
Section: Chapter 1: a Review Of Invertebrate Predation On Aposematic mentioning
confidence: 99%